Adaptive realities : effects of merging physical and virtual entities - Fletcher, Lauren Jean (Rhodes University, Faculty of Humanities, Department of Fine Art, 2015)
In the worlds of virtual reality, whole objects and bodies are created in an immaterial manner from lines, ratios and light pixels. When objects are created in this form they can easily be manipulated, edited, multiplied and deleted. In addition, technological advances in virtual reality development result in an increased merging of physical and virtual elements, creating spaces of mixed reality. This leads to interesting consequences where the physical environment and body, in a similar vein to the virtual, also becomes increasingly easier to manipulate, distort and change. Mixed realities thus enhance possibilities of a world of constantly changing landscapes and adjustable, interchangeable bodies. The notions of virtual and real coincide within this thesis, reflecting on a new version of reality that is overlapped and ever-present in its mixing of virtual and physical. These concepts are explored within my exhibition Immaterial - a creation of simulated nature encompassing a mix of natural and artificial, tangible and intangible. Within the exhibition space, I have created a scene of mixed reality, by merging elements of both a virtual and physical forest. This generates a magical space of new experiences that comes to life through the manipulated, edited, morphed and re-awakened bodies of trees.
Keywords: Virtual reality in art; Reality in art; Art, Modern -- 21st century; Art, Modern -- 21st century -- Themes, motives; Perception